Cell suspension culture of Zedoary (Curcuma zedoaria Roscoe) - Tuan, Vo Chau; Hoang, Vu Duc; Loc, Nguyen Hoang (VNU Journal of Science: Natural Sciences and Technology; Vol 27 No 1, 2011)
Abstract. We report here the protocol for Zedoary ( Curcuma zedoaria Roscoe) callus and cell suspension cultures. The MS medium supplemented with 2% sucrose, 1.0 mg/l 2,4-D and 1.0 mg/l BA was effective for callus induction from in vitro leaf-base explants of Zedoary. During subcultures, secondary proliferated calli were subsequently produced from initial induced calli on the MS medium with 0.5 mg/l 2.4-D and 0.5 mg/l BA. These calli were light yellow in color, compact and friable. The cell suspension culture for Zedoary was established using 3 g fresh weight inoculum in a batch culture on the MS medium supplemented with 3% sucrose, 1.5 mg/l 2,4-D and 0.5 mg/l BA. The highest biomass of 10.44 g  fresh weight (0.66 g dry weight) was obtained after 14 days of culture in 50 ml liquid medium of 250 ml Erlenmeyer flask with shaking speed of 120 rpm. Results from this study might be a well established foundation for further studies on Curcuma zedoaria Roscoe in order to serve as a potential source for secondary metabolites production in large scale. Keywords: Callus, cell biomass, cell suspension, Curcuma zedoaria , medicinal plant